KELIMPAHAN DAN KEANEKARAGAMAN JENIS BURUNG DI HUTAN MANGROVE KPHL GUNUNG BALAK - Iswandaru, Dian; Amrullah Khalil, Abdul Rouf; Kurniawan, Beny; Pramana, Rudi; Febryano, Indra Gumay; Winarno, Gunardi Djoko (Indonesian Journal of Conservation, 2018)
The diversity and abundance of bird species in an area can indicate how the conditions in the area, such as mangrove forest which are the habitat of various species of wild bird. The purpose of study was to analyzing of relative abundance and diversity of birds in the mangrove forest of KPHL Gunung Balak. Data collection using the explore method in a habitat (field to field method). The result of study record was 30 species of birds from 9 family with total number 671 individuals. Analyzing showed the highest abundance of species little egret (Egretta garzeta) is 8.79% and the smallest abundance of species white-breasted Kingfsher (Halcyon smyrnensis) is 0.15%. Shanon-Wienner diversity index shows as medium scale with the value 3.13 which means that the condition of mangrove forest ecosystem in KPHL Gunung Balak is relatively good to support the life of wild birds.